Pengaruh Kecerdasan Emosional, Kecerdasan Intelektual, dan Kecerdasan Spiritual Terhadap Kinerja Auditor - Denada Agustia Nanda; Cris Kuntadi (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aims to determine the influence of emotional intelligence, intellectual intelligence and spiritual intelligence on auditor performance. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Emotional intelligence has a significant positive effect on auditor performance; 2) Intellectual intelligence has a significant positive effect on auditor performance; and 3) Spiritual intelligence has a significant positive effect on auditor performance. This shows that as emotional intelligence, intellectual intelligence and spiritual intelligence increase, the auditor's performance will also increase.